The Principle of Exhaustion of Intellectual Property Rights in Jordanian Legislation - Ammar Mahmoud Ayoub Al-Rawashdeh (Global Writing Academica Researching & Publishing, 2023)
Although the principle of the exhaustion of intellectual property rights has not been adequately studied and explained by law makers, and despite the importance of this principle, which reduces the legal protection of intellectual property rights. Although this principle operates in many countries of the world, the Jordanian legislature has not regulated the subject of the principle of the exhaustion of intellectual property rights in clear and explicit terms, particularly in Jordanian legislation governing intellectual property rights.